Stereotype Against Women in Arabic Domestic Products Seen from Gender Bias Perspective - Raden Ahmad Barnabas; Analisa Apriliani; Nabila Rasyidah (Alfaz (Arabic Literatures for Academic Zealots), 2020)
The research aims to find out the manifestations of gender bias in the indications for the use of domestic products that are frequently used and circulated in the Arab world. It is known that they often use the formulas of orders to address the feminine, especially for products related to food, laundry and spices. This indicates that the Arab Arab society views women as human beings whose jobs are limited to housework only. The research uses the descriptive approach by examining the uses of command formulas in the products circulating in the Arab community. The results of viewing 15 products indicate that 9 of them use the masculine commands, 5 of them use the feminine commands, and one of them uses the infinitive. The commands for the masculine that are obtained are: Empty, Open, Rise, Add, Place, Press, Wash, and be included in Drinks, Hand Wash, Canned Beverages, Booklets, French, Liquid Hand Cleaner, Bathroom Cleaners, Tile Cleaners, Capillaries, and Toys for Children. The feminine commands that are found in the 5 products are: dress up, wear, make sure, fry, and most of them are included in spices, hand washing, laundry, toilet deodorants, cooking oil and cheese. As for the source, to indicate the matter, he uses one product, which is anti-bacterial soap.